The art of custom sneakers how to create one-of-a-kind kicks : paint, splatter, dip, drip, and color - Crews, Xavier (Rockport Publishers, an imprint of The Quarto Group, 2023)
With Art of Custom Sneakers, learn to make your own one-of-a-kind kicks from YouTube superstar Xavier Kickz.